Perfusionists’ Perception of a Blended Training Process in the Management of Extracorporeal Membranes - Boude, Oscar; Bravo Pineda, Carol (International Journal of Online and Biomedical Engineering (iJOE), 2023)
During the SARS-CoV-2 pandemic, many challenges were faced in the global healthcare system, one of which was the lack of competent professionals to implement therapies such as extracorporeal membrane oxygenation (ECMO), which proved to be lifesaving during the H1N1 virus infection. In response to this need, this project aimed to determine the characteristics of a blended training process to contribute to the development of competencies in the management of ECMO therapy and to understand the perception of participants regarding this training process as a suitable strategy for competency development. A mixed design with a descriptive scope based on design-based research was used. The main results indicated that the designed learning environment was suitable for competency development in ECMO therapy management, as well as the importance of including high-quality simulation scenarios in the development of skills for managing this type of therapy. However, the most significant impact was observed in the development of competencies and skills of the participating healthcare professionals through the process of feedback.